Resonant Leadership. An analysis through discussion groups. - Peña Acuña, Beatriz; Parra Meroño, María Concepción; Beltrán Bueno, Miguel Angel (Historia y Comunicación Social, 2014)
This article aims to delve into the qualitative analysis, through the results of several focus groups, in order to discover how such leadership is perceived by young people who have alternated studies with part-time work and have some professional experience and teamwork. This type of leadership comes at a cultural moment where emotional intelligence has become a commonplace in schools, business and personal, in an occasion where this type of intelligence is promoted, estimated and found increasingly as necessary.